2014
DOI: 10.1088/0960-1317/24/4/045014
|View full text |Cite
|
Sign up to set email alerts
|

Micro ultrasonic powder molding for semi-crystalline polymers

Abstract: The present paper introduces micro ultrasonic powder molding (micro-UPM), a novel method for forming micro semi-crystalline polymer parts. In the proposed method, semi-crystalline polymer powder is rapidly heated and plasticized by ultrasonic vibration, after which the microcavity is filled with the melt under sonotrode pressure (PU) to form a variety of micro polymer parts. Differential scanning calorimetry, scanning electron microscopy, and nanoindentation tests demonstrate that micro-UPM UHMWPE (ultra-high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…UHMWPE is widely used in medical, industrial, military and consumer applications [11]. Due to its high molecular weight which induces a very high melt viscosity, UHMWPE parts cannot be produced easily by many conventional methods, such as extrusion and injection moulding, [12,13]. UHMWPE is processed by ram extrusion and compression moulding [14] with a reported density of 0.936 g/cm 3 , ultimate strength of 33.5 MPa and elongation of 380.4% [15].…”
Section: Ultra High Molecular Weight Polyethylene (Uhmwpe)mentioning
confidence: 99%
“…UHMWPE is widely used in medical, industrial, military and consumer applications [11]. Due to its high molecular weight which induces a very high melt viscosity, UHMWPE parts cannot be produced easily by many conventional methods, such as extrusion and injection moulding, [12,13]. UHMWPE is processed by ram extrusion and compression moulding [14] with a reported density of 0.936 g/cm 3 , ultimate strength of 33.5 MPa and elongation of 380.4% [15].…”
Section: Ultra High Molecular Weight Polyethylene (Uhmwpe)mentioning
confidence: 99%
“…The molecular chains at the interface would move and entwine through one another. From the rheological tests, the degree of entanglement of SLL‐5 was greater than that of GUR 4150, resulting in a higher degree of interpenetration/infusion of the former's molecular chains and, thus, the generation of more severe interfacial defects between its thin layers . In addition, SEM micrographs revealed a higher number of large voids and pores in the nascent powders of SLL‐5.…”
Section: Resultsmentioning
confidence: 99%
“…The research works of Fairbanks [10], Paul and Crawford [11], Matsuoka [12], Kellomäki and Törmälä [9], Liang et al [13] and Zeng et al [14] were identified as ultrasonic compression molding. In all of them, the raw material is directly poured into the mold cavity, compacted by the sonotrode, and plasticized by ultrasonic energy inside the mold cavity.…”
Section: Standardization Of Terminology Used In Ultrasonic Moldingmentioning
confidence: 99%